Revolutionary Teaching Approaches: Exploring the Educational Landscape in Pakistan via Outcome-Based Education - Lama , Alma Vorfi; Sain, Zohaib Hassan; Dermawan, Oki; Thelma, Chanda Chansa; Agoi, Moses Adeolu (Ali Institute or Research and Publication, 2024)
Particular emphasis on the Outcome-Based Education (OBE) paradigm, this research aims to investigate the innovative teaching approaches used in Pakistan's educational system. Pakistan is encountering several obstacles to preparing its educational system for the 21st century's demands. As a result, there is a crucial need for innovative methods of instruction. To solve the inadequacies associated with conventional learning methods that rely on memory, transformative pedagogies emphasise student-centred modern ideas and practices. This research investigates the adoption of online learning environments (OBE) in Pakistani schools and its impact on learner participation, critical thinking, and adaptability. The document acknowledges both possibilities and problems, especially about incorporating technology. Some of the constraints include limited resources and cultural expectations. A methodology that utilises many methods, including interviews, observations, and document analysis, was used during an academic year to contribute to the results. The findings of the study indicate that there are a variety of ways in which OBE is implemented, that there is a positive connection between transformational pedagogies and learner engagement, and that there are disparate effects on students at various educational levels. Among the suggestions that have been made in light of the findings are establishing a uniform OBE framework, developing faculty, and including technology. The long-term impacts and the influence of technology and community participation will be the prime focus of study in the future. The findings of this study provide essential insights that may be used to develop a dynamic educational system in Pakistan that can accommodate the demanding requirements of the changing global scene.